2018
DOI: 10.1111/1754-9485.12701
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of dynamic contrast‐enhanced MRI derived volume transfer constant with histological angiogenic markers in high‐grade gliomas

Abstract: The K derived from DCE-MRI can reflect the VEGF expression of high-grade gliomas but not the MVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
4
3
0
Order By: Relevance
“…Our study also demonstrated that K trans and V e were correlated with VEGF expression in gliomas. The conclusions clarifying K trans was correlated with VEGF expression in gliomas were consistent with our findings (26,27). Pang et al published that cerebral blood flow (CBF) derived from ASL also positively correlated significantly with VEGF expression in gliomas (28).…”
Section: Discussionsupporting
confidence: 91%
“…Our study also demonstrated that K trans and V e were correlated with VEGF expression in gliomas. The conclusions clarifying K trans was correlated with VEGF expression in gliomas were consistent with our findings (26,27). Pang et al published that cerebral blood flow (CBF) derived from ASL also positively correlated significantly with VEGF expression in gliomas (28).…”
Section: Discussionsupporting
confidence: 91%
“…A similar finding was expressed very recently in a breast cancer model [ 36 ] and by Di et al. [ 19 ]. MVD differing significantly between prognostic groups supports that differences exist, but that DCE-MRI cannot show them.…”
Section: Discussionsupporting
confidence: 87%
“…This finding corroborates the idea that large vessels and total vascularity of the examined tissue contribute more to the measurement than the sheer density of many small vessels. A similar finding was expressed very recently in a breast cancer model [36] and by Di et al [19]. MVD differing significantly between prognostic groups supports that differences exist, but that DCE-MRI cannot show them.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our results are in agreement with some previous reports. For example, in gliomas, also a positive correlation between VEGF and K trans was observed [2729].…”
Section: Discussionmentioning
confidence: 99%